GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 2892 species occurrences available in GBIF matching the query: TaxonKey: Limnomedusae. The dataset includes 2892 records from 59 constituent datasets: 4 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 11 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 5 records from Zoology (Museum of Evolution - Uppsala). 3 records from AM: Freshwater Invertebrates (1900-2005). 3 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 3 records from Lund Museum of Zoology (MZLU). 20 records from CAS Invertebrate Zoology (IZ). 11 records from Colección de Zoología Invertebrados - Otros invertebrados. 1 records from Norwegian Biodiversity Information Centre - Other datasets. 28 records from Museum of Comparative Zoology, Harvard University. 38 records from Naturalis Biodiversity Center (NL) - Cnidaria. 1 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 25 records from Invertebrates Collection of the Swedish Museum of Natural History. 261 records from NMNH occurrence DwC-A. 12 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from Diveboard - Scuba diving citizen science observations. 3 records from University of Ghent - Zoology Museum - Invertebratacollectie. 4 records from naturgucker. 9 records from UMZC Zoological Specimens. 7 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 2 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 6 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 14 records from Northern Territory Museum and Art Gallery provider for OZCAM. 7 records from SOMBASE BIOCONSTRUCTORS. 1 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 220 records from Natural History Museum (London) Collection Specimens. 1 records from Akita Prefectural Museum＋Cnidarians Specimens of Akita Prefectural Museum. 1 records from UAM Invertebrate Collection (Arctos). 1 records from Marine specimens of Misaki Marine Biological Station, School of Science, University of Tokyo. 123 records from RBINS collections. 1 records from SOMBASE. 4 records from NODC WOD01 Plankton Database. 1 records from Hexacoral Database. 17 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 15 records from Gwaii Haanas Invertebrates (OBIS Canada). 76 records from SINBIOTA - marine data (OBIS South America, BRAZIL). 1 records from MarBEF Publication Series data (EurOBIS). 1 records from Individual Sightings. 11 records from Invertebrate Zoology Division, Yale Peabody Museum. 19 records from IndOBIS, Indian Ocean Node of OBIS. 6 records from invertebratezoology. 8 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 6 records from Marine invertabrate(ECHINODERMATA) specimen database of Osaka Museum of Natural History. 3 records from KUBI Invertebrate Zoology Collection. 11 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 12 records from Collection Cnidaria SMF. 4 records from Queensland Museum provider for OZCAM. 11 records from Geographically tagged INSDC sequences. 38 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 2 records from Cnidaria MZS. 1 records from Marine Conservation Society - Seasearch Marine Surveys. 1 records from Queen Victoria Museum Art Gallery provider for OZCAM. 1742 records from United States Geological Survey Nonindigenous Aquatic Species Database. 3 records from NCSM Invertebrates Collection. 6 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 10 records from Australian Museum provider for OZCAM. 53 records from Occurrences in SinBIOTA. 1 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions.
Keywords: GBIF; biodiversity; species occurrences